ISLAMIC LAW PERSPECTIVE ON LGBT BEHAVIOR (LESBIAN, GAY, BISEXUAL AND TRANSGENDER) - H. M Umar (Yayasan Literasi Kita Indonesia, 2021)
This paper is entitled Perspective of Islamic Law on LGBT Behavior (Lesbian, Gay, Bisexual, and Transgender) which explains that as khal?fah, humans must submit, obey, obey, and serve Allah-not to others-in a broad sense based on the provisions which is stated in shar?'ah. For the convenience of carrying out this great mandate, Allah has equipped with super complete facilities starting from the mind, heart, five senses, sent by the prophet and given the book of the Qur'an as the main guide, although not a few people are still lost. As humans who have external dimensions, humans are given the freedom to enjoy their needs while in the world, including the need to eat, drink, and their biological needs (sexuality). The fulfillment of these needs must be in line with the demands of religion, it should not be as human. That means that human life, both in the spiritual dimension and in the worldly dimension, all of his actions are very tied to the provisions of Allah in this case is shar?'ah.